The High School to University Transition: Exploring the interplay of territory, socioeconomic factors, and gender dynamics - Andrea Priulla; Martina Vittorietti; Vincenzo Giuseppe Genova; Massimo Attanasio (PLoS ONE, 2025)
Education inequalities persist globally, particularly in Italy, often influenced by factors beyond student ability. This paper aims to study the pure territory effect on education inequalities controlling for other factors such as gender, socioeconomic status, and high school performance. As in a clinical study, we evaluate the effect of multiple treatments represented by territorial clusters on the students’ enrolment choices. The inverse of propensity score estimates obtained with a gradient-boosted model (GBM) procedure are used as weights of a multinomial logistic regression model to evaluate the probability of enrolling at the university inside or outside their own place of residence. The study highlights the importance of considering the complex interplay between territory and economic variables in explaining inequalities in the transition from high school to university. Especially in northern regions, we show that the territorial effect on mobility choices, was covered by socioeconomic status and previous educational attainment. In the southern regions, the results highlight a more pronounced territorial heterogeneity regarding the choice to move to another region compared to northern regions.